Hypoglycemic and antilipidemic potential of non-alkaloid from Galega officinalis extract in experimental diabetes mellitus - Hachkova, Halyna; Pokynbroda, Tetiana; Sybirna, Nataliia (Bìologìčnì studìï, 2025)
Introduction. Dyslipidemia is a significant risk factor for cardiovascular disease in patients with diabetes mellitus, especially of type 2. The search for biologically active compounds derived from natural products capable of correcting lipid metabolism is a promising direction in the development of effective and safe dyslipidemia therapy. This study compared the hypoglycemic and antilipidemic potential of the non-alkaloid extract of Galega officinalis and the official herbal medicinal product Arfazetyn under experimental diabetes mellitus. Materials and Methods. Experimental diabetes mellitus was induced by intraperitoneal administration of streptozotocin. The study utilized a non-alkaloid fraction of Galega officinalis extract stabilized with biosurfactants – products of Pseudomonas sp. PS-17 biosynthesis – and the official herbal preparation Arfazetyn. To assess the hypoglycemic effect of the G. officinalis extract and Arfazetyn, glycated haemoglobin and blood glucose levels were measured, an oral glucose tolerance test was performed, and the area under the glycemic curves was calculated. To evaluate the corrective effect of the investigated herbal preparations on lipid metabolism, lipid profile analysis was conducted (total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, and triglycerides). Results. The results indicate that the non-alkaloid fraction of Galega officinalis extract effectively lowers blood glucose and glycated hemoglobin levels to within the physiological range, while also improving glucose tolerance under experimental diabetes mellitus conditions. Moreover, this extract demonstrated a higher hypoglycemic potential than the official herbal medicinal product Arfazetyn. Additionally, administration of the G. officinalis extract contributed to normalizing total cholesterol, low-density lipoprotein cholesterol, decreasing triglycerides, and increasing high-density lipoprotein cholesterol content. Conclusion. The established hypoglycemic potential of the non-alkaloid fraction of Galega officinalis extract, its ability to correct manifestations of dyslipidemia under experimental DM, confirms its therapeutic potential in managing lipid disorders and reducing associated cardiovascular risks.